Gender Dimensions of Investment Climate Reform: A Guide for Policy Makers and Practitioners - Simavi, Sevi; Manuel, Clare; Blackden, Mark C. (The World Bank, 2010)
Promoting women’s economic empowerment is increasingly seen as one of the most important driving forces behind economic growth and the fight against poverty. Women’s economic participation as entrepreneurs, employees, and leaders is recognized as a measure of a country’s dynamism and viability.This main goal of this volume is to provide fresh thinking on how to solve common issues women entrepreneurs and employees face in the investment climate area. It presents actionable, practical, replicable, and scalable tools to promote gender-sensitive investment climate reforms that would equally benefit both women and men. Specifically, the book seeks to enable development practitioners and policy makers who are not gender specialists to diagnose gender issues in an investment climate reform area, design creative and practical solutions and recommendations to address gender constraints, and to oversee the effective monitoring and evaluation of the implementation of those recommendations.This guide highlights the economic rationale for gender inclusion in investment climate reform work and outlines the broader overarching framework within which gender-informed investment climate work can take place. It also provides the monitoring and evaluation framework, with particular emphasis on establishing appropriate baselines to facilitate the measurement of gender-informed changes in the business environment. A step-by-step project management process gives the reader specific guidance on key investment climate areas, namely: (i) business start up and operation, (ii) business taxation, (iii) trade logistics, (iv) special economic zones, (v) alternative dispute resolution, (vi) investment policy and promotion and (vii) secured lending.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; empowerment / empoderamento; entrepreneurship / empreendedorismo; gender / género

Gender and poverty in Mozambique - Tvedten, Inge (CMI Brief, 2010)
Gender equality and women’s empowerment are high on the government and donor agendas in Sub-Saharan Africa, but have largely failed to have an impact. Rather than ‘mainstreaming’ gender, more attention to the variations in the position of women is necessary. In a series of three studies on gender policies and the feminisation of poverty in Mozambique, significant differences were found between the north and the south as well as between rural and urban areas. Such variations are essential to understand in order to design relevant policies and interventions for improving the conditions for women in the country.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; empowerment / empoderamento; gender / género; poverty / pobreza; ⛔ No DOI found

Género e pobreza em Moçambique - Tvedten, Inge (CMI, 2010)
A igualdade de género e o empoderamento das mulheres estão no centro das agendas do governo e dos doadores na África Sub-Sahariana, mas no geral não conseguiram ter impacto. Mais do que a ‘integração’ do género, é necessária mais atenção às variações da posição das mulheres. Numa série de três estudos sobre políticas de género e feminização da pobreza em Moçambique, foram encontradas diferenças significativas entre o norte e o sul, bem como entre as áreas rural e urbana. É essencial que se compreendam estas variações para se desenhar políticas e intervenções relevantes para a melhoria das condições das mulheres no país.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; empowerment / empoderamento; gender / género; poverty / pobreza